Engineering manpower and training needs of the various industries vis-a-vis curricular training programs in selected engineering schools - Viray, Francisco L.
The study is based on the result of a survey conducted among establishments in mining and quarrying, manufacturing, electricity, gas and water; construction; transport, storage and communications and banking located in Regions 4, 7, 10, 11 and NCR. The study shows that : (a) engineering graduates are mostly employed either in management/administrative or are doing low level technologies' work and only a small fraction of them are employed in work that requires engineering skills such as design and research and development; (b) engineering education is perceived to be either adequate or inadequate depending on whether the operation of the compan is specialized or not; (c) most companies provide for the training needs of their newly hired engineering graduate especially in management or in specialized technical skills, through on the job or in house trainings; and (d) companies still deem that the following must be effected to uplift engineering education : more time for on-the-job trainings, improve facilities, improve curriculum and improve teaching faculty.